2018
DOI: 10.4102/sajhrm.v16i0.1010
|View full text |Cite
|
Sign up to set email alerts
|

Reward preferences in South Africa’s media industry

Abstract: Orientation: Employee remuneration is a key driver of employee engagement and thus organisational performance. A thorough understanding of employee needs is essential to enable management to develop an equitable mix in reward strategy.Research purpose: The purpose of this study was to examine context-specific reward preferences in order to determine the overall reward preferences of employees in the media industry with the aim of improving existing reward strategies.Motivation for the study: The focus on rewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The services of a university statistician were procured to assist with the data analysis. The data were analysed using a three-stage data analysis process (Bussin & Thabethe, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The services of a university statistician were procured to assist with the data analysis. The data were analysed using a three-stage data analysis process (Bussin & Thabethe, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative survey research design was chosen in this study to reach a large portion of participants in a fast-moving consumer goods organisation within a set period. The design was cross-sectional to include a view of all generational cohorts at one point in time (Bussin & Van Rooy, 2014;Bussin & Thabethe, 2018;Moore & Bussin, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Diseko (2015), the development of public servants can improve their efficiency in service delivery. Bussin and Thabethe (2018) found that employees aged between 19 and 29 years had a higher preference for learning and development of career paths compared to other groups. Barkhuizen (2013) found that those employees with a lower level of education, such as a Bachelor's degree experienced fewer talent development opportunities compared to those with postgraduate qualifications in government institutions.…”
Section: Talent Developmentmentioning
confidence: 92%
“…Despite growing interest in reward preferences locally (e.g. Bussin & Thabethe, 2018;Fobian & Maloa, 2020;Nienaber, Bussin, & Henn, 2011;Snelgar, Renard, & Venter, 2013) and internationally (e.g. Acheampong, 2021;Adinew, 2020;French & Emerson, 2014), there are not only limited instruments available to measure such preferences, but also ease of access to psychometrically sound measures is further challenging (Hoole & Hotz, 2016;Victor & Hoole, 2017).…”
Section: Introduction Orientationmentioning
confidence: 99%